Victorian Alpine Plot Network (Alpine Summit Plots): Lowland-to-highland Roadside Transects 4WD Tracks Data, South-East Highlands, Australia, 2016 - John Morgan (TERN Australia, 2018)
This Victorian Alpine Plot Network Road Transects 4WD Track Data Package comprises transect-based vegetation data for two Lowland-to-highland 4WD Roadside Transects in the South-East Highlands, Australia. These data have been used against background quadrat data to test a hypothesis about roads as vectors for dispersal of invasive species. Plots are located at altitudinally stratified intervals along two altitudinally-stratified transects. The transects follow major roads and management tracks in the Victorian Alps. Each track is divided into altitudinal sectors in which a single plot is situated. Within each plot, all species are identified and are assigned abundance and cover scores. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.